teaching and learning philosophy in the daily interaction singularity (2013)
This writing describes the possibilities and the limitations that are brought into play when teaching philosophy from what we understand of this activity, and from the ways to assume the social interaction’s patterns, configured by speech, knowledge, power and desire relationships. The purpose is to make visible the practices that take place when teachers, students and philosophers (throughout their production) meet in academic sceneries of professional training, where philosophizing takes different ways and senses in so far as it doesn’t accept hegemonic conceptions and speeches, nor the absence of thinking. Learning philosophy happens within this frame.